2018
DOI: 10.1039/c8tc02982b
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted synthesis of cyclen functional carbon dots to construct a ratiometric fluorescent probe for tetracycline detection

Abstract: Fluorescent carbon dots were synthesized by microwave irradiation of cyclen and citric acid to construct a ratiometric probe for tetracycline detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(46 citation statements)
references
References 36 publications
0
46
0
Order By: Relevance
“…Among the bottom-up approaches, the microwave pyrolysis method has been well-established due to the rapid synthesis and commercialization (Schwenke et al, 2015; In et al, 2017; Rai et al, 2017; Jiang et al, 2018; Shen et al, 2018). Zhu et al reported a facile microwave pyrolysis approach to synthesize CQDs by combining poly(ethylene glycol) (PEG200) and a saccharide (glucose, fructose, etc.)…”
Section: Synthetic Methodsmentioning
confidence: 99%
“…Among the bottom-up approaches, the microwave pyrolysis method has been well-established due to the rapid synthesis and commercialization (Schwenke et al, 2015; In et al, 2017; Rai et al, 2017; Jiang et al, 2018; Shen et al, 2018). Zhu et al reported a facile microwave pyrolysis approach to synthesize CQDs by combining poly(ethylene glycol) (PEG200) and a saccharide (glucose, fructose, etc.)…”
Section: Synthetic Methodsmentioning
confidence: 99%
“…CDs prepared from citric acid and a nitrogen dopant and also precursors which already possess fluorescence are the limit of molecular states' ability to explain CDs PL. 31,131,132 Based on the trends in recent CDs literature, it appears that a surface state controlled PL will be investigated more deeply in the future.…”
Section: Recent Developments In Understanding Carbon Dots Photoluminementioning
confidence: 99%
“…Recently, a new ratiometric uorescence probe based on carbon dots was further developed for detecting TC. 12,17 Liking metal-organic framework materials (MOFs), twodimensional metal-organic framework nanosheets are coordinately assembled by metals and organic ligands. Compared with MOFs, MOFs nanosheets have many advantages, such as rich active sites, large specic surface area, high aspect ratio, adjustable porous structure and chemical composition, as well as ultra-thin thickness, which are widely used in the elds of catalysis, gas separation and chemical sensing.…”
Section: Introductionmentioning
confidence: 99%